Capitalism and Social Mobility Presented in Paul King’s Wonka (2023) - Zuyyina Lutfi Kusuma Wardani; Ana Widiyanti (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2026)
This research aims to analyze: 1) the representation of capitalism in Paul King’s Wonka (2023), and 2) the capitalism leads to social mobility in Paul King’s Wonka (2023).This research uses a descriptive qualitative method to analyze the film of Wonka (2023) directed by Paul King as the object of research. The data collection methods include watching, reading, identifying, classifying, and selecting. The researcher utilizes Karl Marx theory of Capitalism to analyze the data through the steps of displaying, explaining, and interpreting. The result of this research shows that: 1) the representation of capitalism in in Paul King’s Wonka (2023) including capitalism is shown through the practice of exploitation, class inequality, and monopoly by the upper class that controls the means of production, 2) the capitalism leads to social mobility in Wonka (2023). Including collective resistance to an oppressive system. The protagonist and his colleagues managed to improve their social position not because the capitalist system provided opportunities, but because of their class consciousness and collective struggle against injustice.